Does entrepreneurship education and culture promote students' entrepreneurial intention? The mediating role of entrepreneurial mindset - Mukhtar, Saparuddin; Wardana, Ludi Wishnu; Wibowo, Agus; Narmaditya, Bagus Shandy (Cogent education, 2021)
This study aims at examining the relationship between entrepreneurship education, culture, and the entrepreneurial intention of college students as well as investigating the moderating role of the entrepreneurial mindset. Structural equation modeling was adopted to gain a detailed understanding of the influence among variables. This study involved approximately 376 university students who enrolled in the entrepreneurship course. The findings indicate that the entrepreneurial mindset has successfully accelerated the entrepreneurial intention of university students. Partially, entrepreneurial culture has an impact on entrepreneurship education and entrepreneurial intention. Additionally, both entrepreneurship education and entrepreneurial culture have a robust correlation with students' entrepreneurial mindset. Contrary to expectations, this study did not find a significant difference between entrepreneurship education and students' entrepreneurial intention. These results imply that the university has positioned itself as a critical intervention in encouraging students' intention through an effective entrepreneurship education model.